Munasabah Al-Qur’an in The Perspective of Islamic Education - Uswatun Chasanah (Proceeding International Conference on Religion, Science and Education, 2023)
The role of munasabah in establishing the relationship of each sentence, each verse, or every surah in the Qur’an cannot be denied. Munasabah can make it easier for Muslims to study the Qur’an. It is imperative as Muslims to know and understand the knowledge of the Qur’an. This study has a mission to examine and understand the values of Islamic education in the meaning of the Qur’anic munasabah. This type of research is in the form of a literature study by reviewing the results of previous research and other primary sources. The results of the study show that the Qur’anic munasabah is a correlation between sentences, between ayat either in one surah or another surah, or between one surah and another. The development of munasabah from time to time has not escaped the role and views of classical and contemporary scholars on the science of munasabah of the Qur’an. Broadly speaking, the science of the Qur’an is mapped into seven kinds and has a very meaningful position and role in understanding the Qur’an. The wisdom behind munasabah is that it helps in the aspect of understanding and interpreting the Qur’an. This includes the role of munasabah in education such as the learning process in the classroom, as well as in studying the educational values contained in the Qur’an, such as the command of teaching and learning obligations and teacher competence.